T2 mapping and post-contrast T1 (dGEMRIC) of the patellar cartilage: 12-year follow-up after patellar stabilizing surgery in childhood. (October 2017) - Moström, Eva Bengtsson; Lammentausta, Eveliina; Finnbogason, Thröstur; Weidenhielm, Lars; Janarv, Per-Mats; Tiderius, Carl Johan
Background: Cartilage degeneration has been reported after recurrent patellar dislocation. However, effects of surgical stabilization in childhood have not yet been described. Purpose: To examine the cartilage quality in very young adults operated with a patellar stabilizing procedure due to recurrent patellar dislocation in childhood, and evaluate if cartilage quality correlates with clinical parameters and patient-reported outcomes. Material and Methods: Seventeen patients were investigated ≥ 5 years (mean = 11.6 years) after patellar stabilizing surgery in childhood. Pre-contrast T2 relaxation times were analyzed in four superficial and four deep patellar cartilage regions of both knees. Two hours after 0.2 mM/kg Gd-DTPA 2 i.v., post-contrast T1 (T1(Gd)) was analyzed in the same regions. Patient-reported outcomes (KOOS, Kujala, and Tegner scores) and recurrence rates were evaluated. Results: Comparing operated to healthy side, neither T2 nor dGEMRIC differed between the operated and the reference knee regarding the superficial half of the cartilage. In the deep half of the cartilage, T1(Gd) was shorter in the central part of the cartilage, whereas T2 was longer medially ( P < 0.05). A low score in the KOOS subscales Symptom and Sports & Recreation, was correlated to the degenerative changes detected by T1(Gd) (r = 0.5, P = 0.041). Conclusion: In general, our findings demonstrate good cartilage quality 12 years after patellar stabilizing surgery during childhood. The subtle changes in T2 and T1(Gd) in the deep cartilage layer may be a result of altered biomechanics, although very early degenerative changes cannot be excluded. The short T1(Gd) centrally may reflect lower glycosaminoglycan content, whereas the increase in T2 medially indicates increased cartilage hydration.